Deliberative Moments: Understanding Deliberation as an Interactional Accomplishment. Issue 3 (27th May 2018) - Sprain, Leah; Black, Laura
Abstract : Deliberation is typically theorized as a normative ideal that can only be accomplished momentarily. Drawing from practical theory, this essay develops the concept of deliberative moments that identifies key elements of how deliberation is coconstructed and accomplished in interaction. Similar to their analog dialogic moments, deliberative moments are intense moments of awareness of the self, the other, and the issue. Deliberative moments involve occurrence of three elements: a reason-giving exchange marked by disagreement, stance indicators of listening and respect, and inclusive discourse. We define each of these categories and provide empirical examples.